Pandion haliaëtus (Accipitridae) - Beutefang - Georg Rüppell; Wilhelm Möller (IWF (Göttingen), 1981)
(en)Osprey (open air shots). Searching flight, flight manoeuvres preparatory to diving, breaking out of a dive, entering the water, struggles with a fish, and transporting a fish are shown. With slow-motion.